Olga Ivanovna Urazova - Article Editorial (Бюллетень сибирской медицины)
The creative biography of Olga Ivanovna Urazova, doctor of medicine, professor of the faculty of pathophysiology of the Siberian State Medical University, is presented. Main fields of her research and public activity are concerned.